Pengaruh Disiplin Kerja, Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT Jasamarga Solo-Ngawi - Vinnasti, Derby; Lamidi (Teewan Journal Solutions, 2025)
The phenomenon underlying this research, the performance of emplyees at PT Jasamarga Solo-Ngawi during the 2022-2023 period tends to decline. The aim of this research is to analyze the influence of work discipline, motivation and work environment on the performance of PT Jasamarga Solo-Ngawi employees.The population of this study was all 173 employees of PT Jasamarga Solo-Ngawi. The sample in this study amounted to 63 people. The sampling technique uses Proportional Random Sampling. Data collection techniques use validity and reliability tests. The data analysis technique uses multiple linear regression analysis, t test, F test and coefficient of determination test. The results of the analysis show that work discipline, motivation and work environment has a positive and significant effect on the performance of PT Jasamarga Solo-Ngawi employees. The results of the analysis of the coefficient of determination are 0.533, meaning that the contribution of the variables of work discipline, motivation and work environment to the performance of PT Jasamarga Solo-Ngawi employees is 53.3%. The remaining 46.7% was explained to be influenced by other variables that were not studied, for example leadership and compensation.